Bioconversion performance and development of black soldier fly (Hermetia illucens L.) on treated cocoa pod husk - Ciptadi Achmad YUSUP; Haryo Tejo PRAKOSO; . SISWANTO; Deden Dewantara ERIS (Menara Perkebunan, 2020)
Indonesia is the third largest cocoa producer in the world, thus the number of cocoa pod husk (CPH) resulted from this activity is abundant. To handle this waste, farmer usually uses it directly as a feed source to small ruminants but this practice is less effective due to its low protein content and it also contains a substantial amount of lignin. Black Soldier Fly (BSF) (Hermetia illucens L.) (Diptera: Stratiomyidae) larvae are known as bioconversion agents that can be fed upon various organic substrates and they are also high protein source. The aim of this research was to evaluate the possibility of BSF grown on CPH based on their relative growth rate (RGR), efficiency of conversion of ingested food (ECI), waste reduction index (WRI), and development time. Body size of the imago from each treatment was also measured. Larvae were fed with fresh CPH (F), fresh blended CPH (B), composted CPH (C), mix of fresh CPH with food waste (F+FW) and mix of composted CPH with food waste (C+FW). Food waste served as a control. The results of this study show that the most ideal treatment that possible to be applied in cocoa plantation was C+FW treatmentwhich gave average prepupal fresh weight of 11.20 g/100 larvae with 18 days of development time. This treatment had the highest value of WRI and RGR among all treatments. Composted CPH that mixed with food waste treatment also had a shorter development time of BSF larvae.